REUSE OF THE INTRAOSSEOUS PART OF THE DENTAL IMPLANT (THE CLINICAL CASE) - V.M. Dvornyk; O.I. Teslenko; L.B. Jerys; H.M. Kuz; H.M. Balia; V.S. Kuz (Український стоматологічний альманах, 2022)
Introduction. Replacement of a small included defect in the frontal area with a fixed structure based on the implant is the optimal solution. It is not always required to remove the intraosseous part of the implant if there is a fracture of the abutment due to mechanical injury on the background of metal fatigue after its prolonged use. First of all, the abutment’s stability and quality of osseointegration should be determined. After all, a well-integrated intraosseous part of the implant can be further used to fix the pin structure a metalceramic crown on it.